5th Anniversary Article: Engineering Precision Medicine (Adv. Sci. 1/2019). Issue 1 (9th January 2019) - Sun, Wujin; Lee, Junmin; Zhang, Shiming; Benyshek, Cole; Dokmeci, Mehmet R.; Khademhosseini, Ali
Abstract : Each person's response to therapy is different. In article number1801039, Ali Khademhosseini and co‐workers discuss engineering approaches for precision medicine. Healthcare could be individualized through personalized cells therapies, controlled drug delivery systems, personalized scaffolds and implants, wearable sensors, point‐of‐care devices, as well as organs‐on‐chip systems.